A novel peer-to-peer SMS security solution using a hybrid technique of NTRU and AES-Rijndael - Al-Bakri, S.H.; Mat Kiah, M.L. (2010)
Short message service (SMS) is a very popular and easy to use communications technology for mobile phone devices. Originally, this service was not designed to transmit secured data, so the security was not an important issue during its design. Yet today, it is sometimes used to exchange sensitive information between communicating parties. This paper proposes an alternative solution that provides a peer-to-peer SMS security that guarantees provision of confidentiality, authentication, integrity and non-repudiation security services. A hybrid cryptographic scheme has been used which combines the NTRU and AES-Rijndael algorithms to achieve more robust functionality. For implementation, a mobile information device application (MIDlet) has been developed in J2ME to introduce a required security services for SMS. The developed application is tested on real equipment such as a Nokia N70. It is able to achieve all the required cryptographic operations completely on the users' mobile phone in less than one second for each operation, and thus the mobile phone performance still remains effective. Â© 2010 Academic Journals.